PENERAPAN SANKSI PIDANA PENELANTARAN ISTRI OLEH SUAMI DALAM RUMAH TANGGA BERDASARKAN STUDI KASUS NOMOR 32/Pid.sus/2013/PN.SLMN - , MOCH REZKY HAKIMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Act number 23 year 2004 about the violence in households ( uu pkdrt ). Containing the criminal acts against violence to women and children, the effort has been initiated a long time in order to create comfortable and happy social environment free of violence. One of the household